ĐẶC ĐIỂM DI TRUYỀN PHÂN TỬ CỦA VI KHUẨN ORIENTIA TSUTSUGAMUSHI GÂY BỆNH SỐT MÒ Ở MỘT SỐ TỈNH PHÍA BẮC - Nguyễn, Văn Minh; Nguyễn, Văn Tình; Phạm, Thị Hà Giang; Trịnh, Văn Toàn; Dương, Tuấn Linh; Võ, Viết Cường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
MOLECULAR CHARACTERIZATION OF ORIENTIA TSUTSUGAMUSHI CAUSING SCRUB TYPHUS IN SOME NORTHERN PROVINCESOrientia tsutsugamushi, a scrub typhus pathogen, an acute, mite-borne, febrile illness that occurs in the Asia-Pacific region. They were diversified by the 56-kDa surface antigen gene (TSA) which was rapidly detected by nested PCR. To investigate the genotypes of clinical variants of O. tsutsugamushi, 149 blood samples were collected from patients with suspected scrub typhus in period August 2016 to August 2017. The results indicated that 47 (31.5%) samples showed positive result for O. tsutsugamushi. Analyzing the collected samples in a time manual showed that cases were almost occurred from May to November. The nucleotide sequences of 56-kDa TSA gene were determined and assessed the relationship among them. The phylogenetic analyses of partial 56-kDa TSA gene sequences demonstrated wide diversity of O. tsutsugamushi genotypes. The sequencing result of 33 samples indicated that the most common genotype was identified to be Karp (63.6%). Other genotypes including Kato, TA763, Gilliam, and other types were also determined as 12.1%, 9.1%, 6.1% and 9.1%, respectively.